The Influence of E-learning Use to Student Cognitive Performance and Motivation in Digital Simulation Course - Tigowati, Tigowati; Efendi, Agus; Budiyanto, Cucuk Wawan (Universitas Sebelas Maret, 2017)
Currently the technology is growing and sophisticated. Technological advances have also entered the world of education. One of them their is online learning. Examples of learning that utilizes technology that is using Schoology and Edmodo. By using Schoology and Edmodo is expected to increase student motivation and learning outcomes. This study investigates whether the use of different learning management would affect (1) the student’s cognitive achievement (2) student’s motivation (3) the level motivation. This research method using mixed methods. The data collection technique using the test method to determine the cognitive performance. Questionnaires and interviews to find the motivation. The analysis of quantitative data using normality test, homogeneity test, tests of balance and hypothesis testing using independent t test, while the analysis of qualitative data using interactive models. Based on the results of the study (1) there are differences in the cognitive performance between classes that use e-learning based Schoology and e-learning based Edmodo. The cognitive performance classes that use Schoology better than the class that uses Edmodo, because schoology easiness to acces, the students has a target value, better understand the lesson and more active in study this may have an effect on cognitive performance.(2) there is a difference in motivation between classes that use e-learning based Schoology and e-learning based Edmodo. Motivation class with Schoology based e-learning is better than classes with e-learning based Edmodo, because schoology can interested in simulation course, more passion, make happy, easier to learn anywhere and more motivated to learn. (3) the level of motivation of students using e-learning based Schoology and Edmodo included in the medium category